Upaya Meningkatkan Aktivitas Belajar dan Kemampuan Literasi Sains menggunakan E-LKPD berbasis Inkuiri Terbimbing pada Materi Laju Reaksi - Herdini Herdini; Martha Larasaty Hutagalung; Sri Haryati; Putri Adita Wulandari (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2026)
This classroom action research addresses the persistent challenge of low student engagement and limited scientific literacy in learning reaction rate concepts. The study investigates the use of guided inquiry–based electronic worksheets (E-worksheets) as an instructional strategy to promote active learning and support the development of scientific literacy skills. Conducted in two action cycles involving 45 eleventh-grade students at SMAN 12 Pekanbaru during the 2023/2024 academic year, the research employed observation sheets and end-of-cycle assessments to evaluate changes in students’ participation and literacy performance. The findings indicate that integrating guided inquiry with digital worksheets fostered more interactive learning experiences and strengthened students’ ability to interpret, analyze, and apply scientific concepts in problem-solving contexts. This study contributes theoretically by highlighting the potential of guided inquiry–based digital learning media to support scientific literacy development within constructivist learning environments, particularly in chemistry education.